APPROACH TO MEASURE OF THE QUALITY OF THE DISTANCE COURSES BY METHODS OF FUZZY LOGIC - Nozdrina, Л.В. (Journal of Information Technologies in Education (ITE), 2014)
The article examines some aspects of evaluation of quality distance learning, in particular distance learning courses. A list of quantitative and qualitative indicators that measure the quality of distance learning courses, and their evaluation in points is offered. In the paper is described the methodical approach of the use of fuzzy logic to evaluate the quality of distance course.